Iron-Chelated Polydopamine Decorated Doxorubicin-Loaded Nanodevices for Reactive Oxygen Species Enhanced Cancer Combination Therapy - Xu-Jing Li (Frontiers in Pharmacology, 2019)
Combination therapy which enhances efficacy and reduces toxicity, has been increasingly applied as a promising strategy for cancer therapy. Here, a reactive oxygen species (ROS) that enhanced combination chemotherapy nanodevices was fabricated based on the Fe-chelated polydopamine (PDA) nanoparticles (NPs). The structure was characterized by dynamic light scattering-autosizer, transmission electron microscopy, energy dispersive spectroscopy, and Fourier-transform infrared (FT-IR) spectrophotometer. The in vitro drug release profile triggered by low intracellular pH indicated that the system demonstrated controlled therapeutic activity. In vitro cell uptake studies showed that doxorubicin (DOX)-loaded Fe-PDA/ folic acid (FA)- polyethylene glycol (DOX@Fe-PDA/FA-PEG) had a strong uptake capacity and can be rapidly internalized by MCF-7 cells. The in vitro experiments demonstrated that DOX@Fe-PDA/FA-PEG triggered the intracellular ROS overproduction, thereby enhancing its therapeutic effect on breast cancer. In summary, this experiment demonstrated the novel DOX-loaded composite NPs used as a potential targeted nanocarrier for breast cancer treatment, which could be a promising therapeutic strategy against breast cancer.